Penilaian Hasil Belajar untuk Siswa Sekolah Dasar - Deni Hadiana (Jurnal Pendidikan dan Kebudayaan, 2015)
This paper discusses the educational assessment of learning outcomes for elementary school students including the authority institution that can strengthen the knowledge, attitudes, and skills through the strengthening of educational assessment by educators, educational assessment by school, and educational assessment by the Government. Based on the results of the study it can be concluded that internal assessment by teachers and school done with various techniques and procedures strengthens authentic assessment in the domain of knowledge, attitudes, and skills. External assessment is conducted by the government through the end of class survey and school final assessment by using the national standard. Graduation of student is the school’s authority by considering the results of assessment by educators, school, and government. Assessment by the government serves as a mapping and selection to higher level of education, that is junior secondary school.ABSTRAK Tulisan ini membahas penilaian hasil belajar untuk siswa sekolah dasar termasuk aspek kelembagaannya yang dapat memperkuat domain pengetahuan, sikap, dan keterampilan melalui penguatan penilaian hasil belajar oleh pendidik, penilaian hasil belajar oleh satuan pendidikan, dan penilaian hasil belajar oleh Pemerintah. Dari hasil kajian, dapat disimpulkan bahwa penilaian internal oleh pendidik dan satuan pendidikan yang dilakukan dengan berbagai teknik dan prosedur dapat memperkuat penilaian otentik dalam ranah pengetahuan, sikap, dan keterampilan. Penilaian eksternal oleh pemerintah dilakukan melalui survei akhir kelas dan penilaian akhir sekolah berstandar nasional. Kelulusan peserta didik dari satuan pendidikan ditentukan oleh satuan pendidikan dengan mempertimbangkan hasil penilaian oleh pendidik, satuan pendidikan, dan pemerintah. Penilaian oleh pemerintah berfungsi sebagai bahan pemetaan dan seleksi ke jenjang pendidikan sekolah menengah pertama.